ANALYSIS OF STUDENTS 'MATHEMATIC PROBLEM SOLVING ABILITY IN LINEAR PROGRAM MATERIALS - Mitra Yeni; Melisa Melisa; hafizah Delyana (Jurnal Equation: Teori dan Penelitian Pendidikan Matematika, 2021)
Problem solving ability is one of the goals of mathematical ability. This study aims to analyze students' mathematical problem solving abilities in linear program material in class XI MIPA IV SMAN 1 Lembah Gumanti. This research uses qualitative research. The research subjects were students of class XI MIPA IV Lembah Gumanti. The research instrument used was a problem solving ability test. The stages of this research are starting from the planning, implementation, and observation processes. The mathematical problem solving problems given are 4 questions that have been validated by mathematical experts. From the results of the research that has been done, there are difficulties in solving the problem solving problems. Students who have low problem solving ability criteria because students do not understand the problem from the problem solving ability so that students have difficulty planning problems from linear program questions. So, students are not able to solve problem solving skills well.Keywords: Problem Solving Ability